Effects of Kin Ball Initiation: Pre- and Post-Pandemic Impact on Palmar Muscle Strength, Endurance, and Coordination in Non-Athlete Participants - Daniel Rosu; Ion-Sebastian Enache; Raul-Ioan Muntean; Valentina Stefanica (MDPI AG, 2024)
The aim of our research is to introduce Kin Ball for the first time in Romania and assess its impact on the motor capacities of practitioners, particularly focusing on its potential contribution to developing motor skills in young students within the academic sphere, despite the challenges posed by the COVID-19 pandemic. Design: A retrospective, case-control study with a focus on four distinct research groups. Setting: The research was conducted in a camp setting, situated in the mountainous region of Bughea de Sus, Romania. Participants: The study included 94 students, comprising 54 boys and 40 girls, with an overall average age of 20.85 ± 2 years. All participants were classified as non-athletes based on their level of sports practice. Interventions: The Kin Ball initiation program, a key component of the study, comprised 20 training sessions conducted in 10-day stages, systematically evaluating participants' motor skills. Main outcome measures: The study assessed palmar muscle strength, endurance, and co-ordination function. Results: Statistical analyses, including the Kolmogorov-Smirnov test, revealed notable differences in the initiation process and significant variations (p < 0.05) in all measurements performed in 2022. In 2019, the tests recorded both significant and statistically insignificant differences, as indicated by the calculation of Cohen's d indicator. Conclusions: The study underscored the influence of reduced movement during the pandemic on motor skills and highlighted Kin Ball's potential as an alternative sport within physical education curricula. Despite lower baseline motor capacities observed in 2022, participants exhibited significant progress, emphasizing Kin Ball's capacity to improve physical skills. These findings underscore the importance of alternative sports such as Kin Ball in fostering holistic personal development and mitigating the impact of pandemic-induced disruptions on motor skills.